Arbuscular mycorrhizal symbiosis induces strigolactone biosynthesis under drought and improves drought tolerance in lettuce and tomato. (16th October 2015) - Ruiz‐Lozano, Juan Manuel; Aroca, Ricardo; Zamarreño, Ángel María; Molina, Sonia; Andreo‐Jiménez, Beatriz; Porcel, Rosa; García‐Mina, José María; Ruyter‐Spira, Carolien; López‐Ráez, Juan Antonio
Abstract: Arbuscular mycorrhizal (AM) symbiosis alleviates drought stress in plants. However, the intimate mechanisms involved, as well as its effect on the production of signalling molecules associated with the host plant–AM fungus interaction remains largely unknown. In the present work, the effects of drought on lettuce and tomato plant performance and hormone levels were investigated in non‐AM and AM plants. Three different water regimes were applied, and their effects were analysed over time. AM plants showed an improved growth rate and efficiency of photosystem II than non‐AM plants under drought from very early stages of plant colonization. The levels of the phytohormone abscisic acid, as well as the expression of the corresponding marker genes, were influenced by drought stress in non‐AM and AM plants. The levels of strigolactones and the expression of corresponding marker genes were affected by both AM symbiosis and drought. The results suggest that AM symbiosis alleviates drought stress by altering the hormonal profiles and affecting plant physiology in the host plant. In addition, a correlation between AM root colonization, strigolactone levels and drought severity is shown, suggesting that under these unfavourable conditions, plants might increase strigolactone production in order to promote symbiosis establishment to cope with the stress. Abstract : The current work shows a comprehensive study covering the effects of drought on plant physiology and mycorrhizal (AM) colonization. We propose that AM symbiosis alleviates drought stress by altering the hormonal profiles and affecting plant physiology in the host plant. A correlation between AM colonization, strigolactone levels and drought severity is shown for the first time.